(untitled) - Charmantray, Franck; Hecquet, Laurence (Comptes Rendus. Chimie, 2025)
Enzymatic carbon–carbon (C–C) bond formation represents an efficient asymmetric alternative for the preparation of multifunctional products. This paper presents an overview of the advances made by engineering a thermostable thiamine-dependent carboligase, transketolase from Geobacillus stearothermophilus (TKgst), for the synthesis of various α-hydroxyketones (aliphatic, hydroxylated, and aromatic). While TKs in cells exclusively transfer a ketol unit from a ketose phosphate to an aldose phosphate Cn leading to a Cn+2 ketose phosphate yielding a reversible reaction, the results reported in this paper showed the wide range of non-phosphorylated substrates accepted by the selected TKgst variants, particularly towards α-ketoacids used as nucleophiles, render the reaction irreversible due to the release of carbon dioxide. To enhance TKgst activity towards the targeted nucleophiles, analogues of pyruvate, and electrophiles such as aliphatic, polyhydroxylated, and aromatic aldehydes, the best variants were selected from libraries created by rational design. As the main hurdle for biocatalytic application is the instability/cost of α-ketoacids, one-pot strategies were performed for in situ generation of α-ketoacids from corresponding amino acids with transaminase or amino acid oxidase. A novel promising promiscuous TKgst reaction based on selective cross-acyloin condensation of two aldehydes, one playing the role of the nucleophile in place of the α-ketoacid and the other aldehyde acting as an electrophile, was also investigated. This original TKgst catalyzed reaction provides atom economy while avoiding carbon dioxide release and achieving similar efficiency compared to the usual pathway.